Mindfulness's moderating role applied on online SEL education - Ho, Chun-Heng; Zhang, Hang-qin; Li, Juan; Liu, An'an (Frontiers in Psychology, 2024)
Mild to moderate depression, anxiety, and stress imbalances are prevalent emotional issues among college students and are primary factors leading to deficiencies in social-emotional skills within this population. Without timely intervention, these mild to moderate emotional issues may escalate into more severe conditions. This not only adversely affects students' physical and mental health and academic performance but also significantly disrupts the normal progression of teaching and the positive functioning of society. Social-Emotional Learning (SEL) programs are effective for building social-emotional skills. However, current research on SEL programs has not adequately addressed the issue of high-quality teacher-student interactions for students who suffer emotional problems. To tackle this issue, this study proposes a curriculum approach that integrates mindfulness with rhythmic music. The research findings indicate that: (1) eighth-note, quarter-note, and sixteenth-note rhythmic music significantly improve the emotional well-being of students with depression, anxiety, and stress imbalances, respectively. (2) The degree of emotional improvement has a certain impact on academic performance. (3) Students with anxiety require more instructional support focused on attention concentration during the early phases of the course; students with depression should not be scheduled for social skills learning modules in the short term and need long-term instructional guidance; individuals experiencing stress imbalances require attention to their personal music preferences and benefit from additional listening activities and exercise. These findings assist teachers in accurately identifying emotional changes among students with emotional problems and managing the patterns of these emotional transitions, thereby providing effective instructional support and promoting highquality interactions between teachers and students. expression but also involve skills in decision-making, goal setting and achievement, as well as managing stress and challenges. Numerous studies confirmed that SEL programs contribute to improving students' emotional health, enhancing life satisfaction, and fostering better interpersonal relationships (